Effects of Exercise Training on Renal Carnitine Biosynthesis and Uptake in the High-Fat and High-Sugar-Fed Mouse - Upadhyay, Aman (Molecules, 2020)
(1) Background: Diet-induced obesity inhibits hepatic carnitine biosynthesis. Herein, the effects of high-fat (HF) and high-sugar (HFHS) feeding and exercise training (ET) on renal carnitine biosynthesis and uptake were determined. (2) Methods: Male C57BL/6J mice were assigned to the following groups: lean control (standard chow), HFHS diet, and HFHS diet with ET. ET consisted of 150 min of treadmill running per week for 12 weeks. Protein levels of γ-butyrobetaine hydroxylase (γ-BBH) and organic cation transporter-2 (OCTN2) were measured as markers of biosynthesis and uptake, respectively. (3) Results: HFHS feeding induced an obese diabetic state with accompanying hypocarnitinemia, reflected by decreased free carnitine levels in plasma and kidney. This hypocarnitinemia was associated with decreased γ-BBH (~30%) and increased OCTN2 levels (~50%). ET failed to improve the obesity and hyperglycemia, but improved insulin levels and prevented the hypocarnitinemia. ET increased protein levels of γ-BBH, whereas levels of OCTN2 were decreased. Peroxisome proliferator-activated receptor-alpha content was not changed by the HFHS diet or ET. (4) Conclusions: Our results indicate that ET prevents the hypocarnitinemia induced by HFHS feeding by increasing carnitine biosynthesis in kidney. Increased expression of OCTN2 with HFHS feeding suggests that renal uptake was stimulated to prevent carnitine loss.